PERKEMBANGAN BAHASA ISYARAT DAERAH DENPASAR - Ni Putu Luhur Wedayanti; Alies Poetri Lintangsari; Gede Ade Putra Wirawan (Masyarakat Linguistik Indonesia, 2021)
Despite the ongoing situational debate about sign language, there is a growing number of sign language usage in the social context in Indonesia. Bali, as one of the centers of Deaf community, provides potential resources for the research of sign language in Indonesia. This research explores the sign language variation in Bali specifically in Denpasar. The studies of sign language and Deaf community is also discussed. The result of this research strengthens the situation of sign language as real language since it provides a complex language variation as found in verbal language.